Actions of Thyroid Hormone Analogues on Chemokines - Paul J. Davis; Gennadi V. Glinsky; Hung-Yun Lin; Shaker A. Mousa (Journal of Immunology Research)
The extracellular domain of plasma membrane integrin αvβ3 contains a receptor for thyroid hormone (L-thyroxine, T4; 3,5,3′-triiodo-L-thyronine, T3); this receptor also binds tetraiodothyroacetic acid (tetrac), a derivative of T4. Tetrac inhibits the binding of T4 and T3 to the integrin. Fractalkine (CX3CL1) is a chemokine relevant to inflammatory processes in the CNS that are microglia-dependent but also important to normal brain development. Expression of the CX3CL1 gene is downregulated by tetrac, suggesting that T4 and T3 may stimulate fractalkine expression. Independently of its specific receptor (CX3CR1), fractalkine binds to αvβ3 at a site proximal to the thyroid hormone-tetrac receptor and changes the physical state of the integrin. Tetrac also affects expression of the genes for other CNS-relevant chemokines, including CCL20, CCL26, CXCL2, CXCL3, and CXCL10. The chemokine products of these genes are important to vascularity of the brain, particularly of the choroid plexus, to inflammatory processes in the CNS and, in certain cases, to neuroprotection. Thyroid hormones are known to contribute to regulation of each of these CNS functions. We propose that actions of thyroid hormone and hormone analogues on chemokine gene expression contribute to regulation of inflammatory processes in brain and of brain blood vessel formation and maintenance.